PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING COMPOSITION (CIRC) PADA KELAS 5 SD NEGERI 096 SARIJADI SELATAN TAHUN AJARAN 2022/2023 - Febi Sulistyo Rini; Ghullam Hamdu; Eva Riyanti (STKIP Subang, 2023)
The purpose of this research was to improve ability of reading comprehension on fifth grade student of 096 Sarijadi Selatan Primary School in academic year of 2022/2023. The type of this research is Classroom Action Reasearch (CAR). This research was done in two cycles. Each cycle consisting of four phases there were planning, acting, observing, and reflecting. Subject of this research was 27 fifth grade student. Data collecting technique used observation, interview, test, and document study. Based on the research findings and the observation of Minimum Mastery Criteria (KKM) namely 75, the average score of students’ ability of reading comprehension on first test before the action done was 60,56. After cycle one, the score increased to 72,22 and at cycle 2 it became 80. The conclusion of this research was the impelementation of Cooperative Integrated Reading Composition (CIRC) model can improve students’ ability of reading comprehension on fifth grade of 096 Sarijadi Selatan Primary School Bandung City in academic year of 2022/2023.